Job Market Driven IT Career Development with Design Thinking Framework & Business Model Mindset - Jacek B. JAKIELA; Joanna M. ŚWIĘTONIOWSKA; Joanna K. WÓJCIK (Communications of International Proceedings, 2021)
One of the critical success factors that drives New Economy development is not only a technology itself but human resources with the right set of skills. The aim of the paper is to pre-sent the original approach that can be used for IT career development. What is more, paper shows how to increase awareness of professional development direction that complies with interests and passions. This should positively affect work motivation level, improve the satisfaction as well as efficiency and effectiveness in the workplace. Our approach is based on Design Thinking framework applied to such activities as discovering ones passion, understanding the professional identity from the perspective of personal resources, ideating possible job positions and testing the different career development paths. It also encompasses several techniques supporting the process, such as Business Model Canvas and Personal Business Model Canvas that have been adopted to describe a work environment in the context of the key components of different job positions and to understand job market requirements. The approach have already been tested during the workshops with students, who will become professional staff members within few years.
Keywords: Career development; Business Model Canvas; Design Thinking; BEAST Project.